Governance of Non-Profit Organizations: A Case of Zakat Institutions in Malaysia - Saad, Ram Al Jaffri; Md Idris, Kamil; Shaari, Hasnah; Sawandi, Norfaiezah; Derashid, Chek (Serials Publications, 2017)
Malaysia, like any other Muslim country, considers the zakat institutions as one of the important contributors to economic development and society in the country.However, there are unresolved issues surrounding zakat institution.Among them is the issue of the inefficiency of the institutions in managing zakat collections.Thus, the purpose of this study is to examine three aspects of the zakat management in Malaysia, namely the collection and distribution of zakat fund performance, zakat governance and zakat collection and distribution innovation.The data were obtained through secondary sources and 14 zakat institutions were selected as a sample.The result of the study shows that the governance of zakat institution was not reached at optimum level where there is a significant surplus of non-distributed zakat funds and less innovation have been done to improve its collection and distribution. The study establishes the need for zakat institutions to improve their governance aspect in term of the performance and innovation towards the collection and distribution of the fund.